Cost of Production, Cost of Operation, and Net Sales to Net Profit - Oktaviano, Benny; Dian Sulistyorini Wulandari; Ade Priyani (Indonesian Journal of Economic & Management Sciences, 2024)
This research aimed to assess the impact of production costs, operating costs, and net sales on the net income of metal and comparable manufacturing companies listed on the Indonesia Stock Exchange during the period 2016–2020, whether individually or collectively. The data collection employed a purposive sampling method. The findings revealed that production costs had a partial impact on net income, whereas operating costs exhibited an influence on net income, while net sales did not. Collectively, the variables of production costs, operating costs, and net sales exerted a significant effect on net income. The R2 test indicated a value of 0.359. These results substantiate that production costs, operational costs, and net sales jointly contribute to the net income of metal and similar manufacturing companies on the Indonesia Stock Exchange for the 2016-2020 period, accounting for 35.9%. This implies that profit in this study is influential, while the remaining 64.1% is influenced by other factors not considered in this research